Influence of shear banding of polymeric fluids on the shape of rheological curves - Kuznetsova, Yuliya Leonidovna; Skul’skiy, Oleg Ivanovich (Computational Continuum Mechanics, 2018)
The recently discovered effect of shear banding in polymer fluids has provoked great interest in studying basic physics underlying this effect, which can also be considered as the main mechanism responsible for the appearance of specific features of polymer liquids in rheometric flows. In this paper, we study the influence of shear banding in polymeric fluids on the shape of the torque-angular velocity curve obtained using a coaxial cylinder sensor system during the experiments on a rotational rheometer. A modified Vinogradov-Pokrovsky model with parameters ensuring а non-monotonic flow curve was used to simulate shear banding. Analytical relations for determination of velocity and stress fields at a given torque are found. A numerical method for establishing stationary solutions from the state of rest is proposed. It was found that the torque-angular velocity curve, which was plotted on the basis of the modified Vinogradov-Pokrovsky model for the controlled velocity of rotation of the cylinder, qualitatively changes its shape under different loading conditions. In addition, the influence of the time of acceleration up to the prescribed velocity of rotation of the inner cylinder (characteristic of any experimental device) on the shape of these curves is investigated. It is shown that the modified Vinogradov-Pokrovsky model with a non-monotonic flow curve predicts the formation of a horizontal section, so-called “plateau”, on the torque-angular velocity curve in the case of the controlled velocity of rotation of the cylinder and the formation of a hysteresis loop at controlled torque. Such a behavior of the obtained curves is in qualitative agreement with the experimental data.